2018
DOI: 10.2139/ssrn.3186985
|View full text |Cite
|
Sign up to set email alerts
|

Female Translation Students' Knowledge and Use of Online Dictionaries and Terminology Data Banks: A Case Study

Abstract: This study aims to determine whether translation students at an undergraduate translation program have sufficient awareness of the availability and usability of online vocabulary and terminology search tools that can be of valid assistance to a translator. The study surveyed 50 female translation students of the Translation Program at Prince Sultan University, Saudi Arabia. The survey consisted of questions about knowledge and use patterns and included texts for translating between English and Arabic. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…The pieces of information the participants of this study reported looking for when consulting the dictionary are similar to those mentioned by the participants in Sabbah and Alsalem (2018). This finding, in particular, signifies a major difference between successful translation trainees and other trainees.…”
Section: Participants' Dictionary Usagesupporting
confidence: 66%
See 4 more Smart Citations
“…The pieces of information the participants of this study reported looking for when consulting the dictionary are similar to those mentioned by the participants in Sabbah and Alsalem (2018). This finding, in particular, signifies a major difference between successful translation trainees and other trainees.…”
Section: Participants' Dictionary Usagesupporting
confidence: 66%
“…With the digital revolution, a common finding that has been supported by the results of the current study is dictionary users' shift to electronic dictionaries (Lew, 2013b). This shift has been confirmed by the results of many studies in the field, including Kodura (2016), Sabbah andAlsalem (2018), andTulgar (2017).…”
Section: Participants' Dictionary Preferencessupporting
confidence: 61%
See 3 more Smart Citations